2023
DOI: 10.1002/adfm.202214301
|View full text |Cite
|
Sign up to set email alerts
|

Customizable Supercapacitors via 3D Printed Gel Electrolyte

Abstract: New manufacturing strategies toward customizable energy storage devices (ESDs) are urgently required to allow structural designability for space and weight-sensitive electronics. Besides the macroscopic geometry customization, the ability to fine-tune the ESD internal architectures are key to device optimization, allowing short and uniform electrons/ions diffusion pathways and increased contact areas while overcoming the issues of long transport distance and high interfacial resistance in conventional devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Consequently, the assembled device maintains stable mechanical and electrochemical properties even after undergoing over 100 consecutive bending cycles. Zhou et al 85 proposed an innovative fabrication method for flexible supercapacitors wherein a gel electrolyte template was initially prepared via 3D printing followed by assembly of electrodes, collectors, and encapsulation materials through the dip-coating technique, thus enabling realization of flexible supercapacitors possessing both an internal three-dimensional structure and overall 3D geometry that can be easily integrated into diverse electronic products ( Fig. 7h ).…”
Section: Flexible Supercapacitorsmentioning
confidence: 99%
“…Consequently, the assembled device maintains stable mechanical and electrochemical properties even after undergoing over 100 consecutive bending cycles. Zhou et al 85 proposed an innovative fabrication method for flexible supercapacitors wherein a gel electrolyte template was initially prepared via 3D printing followed by assembly of electrodes, collectors, and encapsulation materials through the dip-coating technique, thus enabling realization of flexible supercapacitors possessing both an internal three-dimensional structure and overall 3D geometry that can be easily integrated into diverse electronic products ( Fig. 7h ).…”
Section: Flexible Supercapacitorsmentioning
confidence: 99%
“…Liu et al recently reported the digital light processing of supercapacitor devices, where both external and internal architectures were customizable via 3D printed gel electrolytes. [ 186 ] Compared with the planar stacked configuration, the as‐printed device in internal 3D interdigitated configuration offered an increased electrode–electrolyte contact area (by ≈113%), shortened charge transfer pathways, and lowered interface resistances. A high areal device capacity of 282.7 mF cm −2 was achieved consequently, while the conventional supercapacitors in planar stacked configuration exhibited a lower capacity of 205.5 mF cm −2 .…”
Section: Interface Engineering Strategies For 3d Printed Energy Storagementioning
confidence: 99%
“…Microelectronic power sources, therefore, face the multifaceted challenge of integrating safety, cost-effectiveness, small form factors, mechanical flexibility, and exceptional performance. In this context, MXene-based micro-supercapacitors (MSCs) have emerged as a formidable solution, leveraging the intrinsic properties of MXene materials, such as their remarkable electrical conductivity and atomically thin 2D structure [ 4 , 5 , 6 , 7 ]. These properties are pivotal in advancing the charge storage capabilities of MSCs, enabling them to meet the stringent energy demands of 5G-powered devices.…”
Section: Introductionmentioning
confidence: 99%